MODERN APPROACHES OF ESTIMATION OF RISK FACTORS INTERMITTENT INFLUENCE - A. Fadeeva, Svetlana; D. Sitdikova, Irina; N. Mingazova, Elmira; W. Khuzikhanov, Farit; A. Berezin, Veniamin; I. Gerasimova, Ljudmila (Gênero & Direito, 2019)
We studied the quality of three environmental objects of the population living in a large industrial city (atmospheric air, soil and drinking water). We also determined the content and quantity of chemicals in the habitat of the population living near large industrial enterprises. We presented the results of the calculations of hazard indexes (HI), on the basis of which we derived the risk features of the development of non-carcinogenic effects of exposure to the body of chemical compounds (with combined and complex exposure). Non-carcinogenic risk is defined as an indicator of the expected increase in the incidence of the population due to the toxic properties of foreign chemicals in the studied environmental objects. The main objective of our socio-hygienic study was to identify chemical factors in the environment that are potentially hazardous to the life and health of children and adults living within a radius of 4,800 meters from an industrial enterprise in a large industrial city when received in different ways (combined) and assess the risk of violations in human health of varying severity when exposed to non-carcinogenic chemicals